Role and Value of Luminex®-Detected HLA Antibodies before and after Kidney Transplantation - Süsal, Caner; Opelz, Gerhard; Morath, Christian (Transfusion medicine and hemotherapy, 2013)
The complement-dependent lymphocytotoxicity (CDC) method has been the classical technique to detect human leukocyte antigen (HLA) antibodies in sera of patients who are listed for kidney transplantation. Because of the drawbacks of CDC, such as low sensitivity and low resolution in characterizing antibody specificities, the more specific ELISA technology was introduced in the 1990s which utilizes solubilized HLA molecules instead of lymphocytes. During the last 10 years, the introduction of the Luminex-based single antigen bead (L-SAB) technology, which uses recombinant single HLA molecules, allows detection and characterization of HLA antibodies at greater sensitivity than CDC and ELISA. A drawback associated with this technique is that the interpretation of results is demanding and requires comprehensive experience in HLA antibody diagnostics. Herein we discuss the current role and value of L-SAB technology in the clinical management of sensitized kidney transplant recipients.